Respiratory-mucin inhibition of the opsonophagocytic killing of Pseudomonas aeruginosa. - Vishwanath, S (1988)
Pseudomonas aeruginosa is a frequent respiratory tract colonizer in diseases in which mucociliary clearance is defective. The most striking of these is cystic fibrosis. The reasons for this organism's ability to colonize the respiratory tract and to persist there are not fully understood. Earlier studies showed that P. aeruginosa adheres preferentially to tracheobronchial mucin when compared with enterobacteria. We reasoned that if adherence to respiratory mucin protected P. aeruginosa from opsonophagocytic killing, then the ability of this organism to chronically colonize the respiratory tract could be partially explained. Using an opsonophagocytic killing assay with human polymorphonuclear leukocytes, we found that respiratory mucin protected six strains of P. aeruginosa from opsonophagocytic killing but did not protect poorly adhering strains of Escherichia coli, Staphylococcus aureus, or group B streptococci. Incubating P. aeruginosa with the mucin prior to addition to the opsonic assay inhibited phagocytic killing, whereas incubation of polymorphonuclear leukocytes with mucin did not, suggesting that inhibition was not due to an effect of mucin on leukocytes per se but was a consequence of bacterial adherence to mucin. Further studies indicated no decrease in the binding of either antibody or complement component C3 to the bacterial surface in the presence of mucin. This suggests that phagocytic inhibition may be due to a defect in uptake or destruction of mucin-coated bacteria by the leukocytes. Thus, the adherence of P. aeruginosa to respiratory mucin potentially contributes to its persistence in the respiratory tract by interfering with host immune responses.